Legal Analysis of Green Victimology in Environmental and Forestry Crimes - Ningrum, Maya Puspita; Roza, Ahmad Fadhly; Komalasari, Komalasari; Nadapdap, Gindo (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
Environmental and forestry crimes are serious violations that not only damage ecosystems but also threaten human sustainability. This study aims to examine the criminal law policy in addressing environmental crimes based on Law Number 32 of 2009 on Environmental Protection and Management, and to evaluate the application of criminal liability through in absentia procedures in illegal logging cases, as exemplified by the District Court Decision No. 954/Pid.Sus/2022/PN Mks. This research adopts a normative juridical approach with a descriptive-qualitative analysis of primary and secondary legal materials. The findings reveal that while the criminal law policy on environmental protection is normatively robust, its implementation faces challenges such as weak supervision and low public legal awareness. Furthermore, the in absentia mechanism has proven effective in ensuring justice when perpetrators evade legal proceedings, though it raises legal debates concerning the defendant’s right to a fair trial. This study underscores the need to strengthen regulations and procedural safeguards to enhance the effectiveness of environmental criminal law enforcement in Indonesia.